IMPLEMENTASI MEDIA PEMBELAJARAN ANIMASI DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA PADA PEMBELAJARAN PAI KELAS VIII DI SMPIT CAHAYA INSANI KEDU - wawan wawan gunawan sihab sihab (Al Ghazali, 2022)
Sihab, Wawan Gunawan . 2022.Implementation of Animation Learning Media in Improving Students’ Learning Motivation in Class VIII PAI Learning at SMPIT Cahaya Insani Kedu. Thesis, Islamic Religious Education, Faculty of Tarbiyah and Teacher Training at the Islamic Instituse of Nahdlatul Ulama Temanggung. This research is motivated by students who have difficulty in understanding learning because they are fixated on books, the learning carried out tends to be more conventional, and students listen more to the teacher's explanations. The purpose of this study is to describe the use of animation media in increasing PAI learning motivation and to find out the increase in students' learning motivation through the implementation of PAI learning media and to analyze the supporting and inhibiting factors for implementing animation learning media in VIII grade PAI learning at SMPIT Cahaya Insani Kedu. The research method used in this study is a qualitative method. the research approach uses a pedagogic approach. This type of research uses a case study method. The primary data source in this study is the PAI teacher at SMPIT Cahaya Insani Kedu and the secondary data source is the documentation. Data collection techniques were conducted by interview, observation, and documentation. After the data is collected, the next step is data analysis techniques using data reduction, data presentation, and verification. The data validity technique in this study used data triangulation. The research subject in this thesis is class VIII A of SMPIT Cahaya Insani Kedu. The results showed that animation media can help students in carrying out learning, such as stimulating creativity, increasing enthusiasm for learning, and understanding the material more optimally. Increasing students' learning motivation through the implementation of animation media has increased, including media according to the curriculum, choosing the most important materials that can be implemented by animation media, and preparing programs or tools that will be used to support material delivery. Factors supporting the implementation of animated learning media are motivating students to pay attention to the material, making it easier for teachers to provide information, and animation can combine large amounts of scientific data into one. The inhibiting factor is that it requires sufficient computer storage space or memory, and makes web pages quite slow on the computer. Keywords: implementation, learning media, animation.